PENERAPAN DATA MINING UNTUK ANALISIS MARKET BASKET DENGAN ALGORITMA FP-GROWTH PADA PD PASAR TOHAGA - Rusnandi Rusnandi; Suparni Suparni; Achmad Baroqah Pohan (Prodi Pendidikan Teknik Informatika Universitas Pendidikan Ganesha, 2020)
Sales data in 3 different shops (shop, Shop Maker Fernando and Son) at Tohaga Market in the form of PD book transactions are only seen in the absence of follow-up to determine the decision on who will come. Party owner only records the transactions of products sold and only see income per month. But with that data should be utilized to strategize on sales to come. By using the method of Frequent Pattern Growth Algorithm, the store can take decisions which require goods inventory more compared to other goods, and the placement of the goods in accordance with the relationship between the goods that are usually purchased a consumer can also be determined based on a Minimum Support and Minimum Confidence. Based on Market Basket Analysis obtained from the calculation of the Association by using the method of Frequent Pattern Growth Algorithm, then search for the value of the support and confidence to use Association Rules, Rules that are generated will be test by using Software RapidMiner. Then the placement of goods and inventory items in 3 different stores can be controlled with either the service so that the consumer will be increased, which in turn can increase the sales turnover. In this study Support is determined using threshold 40% and 83% Confidence. Having regard to the relationship of support and confidence the store owner can provide and put the items to be sold